A Grammatical Error Analysis in A Fourth Semester Students’ Interview - Murniwati Ndruru; Dwina Putri Ayu Saragih (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Language is one of the means of human communication in interacting with one another. Broadly speaking, language has become part of human life, even a basic human need in carrying out their lives. However, along with the development of the era, the use of English is increasingly being rivaled by the use of slang, especially among students, causing some errors in knowing what the meaning of the word is. To avoid things that cause someone's English to speak English correctly, and then use the method to practice, and understand the word classes contained in grammar. But the most important thing is to master as much vocabulary as possible to improve English perfectly. In this study, researchers obtained data sources by interviewing 4th semester students and 2nd semester students through student social media, namely the Teams application which was carried out online. This study focuses on the analysis of the use of interview grammar, which was obtained using a qualitative descriptive method. The form of presentation is done by descriptive presentation in the form of words or sentences that do not have percentages and numbers. Therefore, the researchers analyzed the data errors according to the category of grouping the types of word classes used so that the researchers got 8 data, where the data had errors in the use of the simple present word class, the use of To be, action verb, and perfect tense.